Do açúcar aos suvs: análise da indústria de transformação pernambucana a partir do século XX. - Araújo, Pedro Gomes Maranhão de (2021)
Economic theories point to the manufacturing industry as a key role for regional development. The contemporary world, in many ways, is the product of industrialization. That said, the work poses the following research problem: what is the importance and effects of the manufacturing industry for the economic development of the Pernambuco state? According to economists, Brazil is going through a deindustrialization process, however some regions may be going against this phenomenon. The Pernambuco state, in the last two decades, presented an effervescence of industrial activity by diversifying its production with structuring projects and investments in industrial hubs. Thus, as a main objective, the thesis proposes to carry out a macroeconomic analysis of the state's manufacturing industry from the ECLAC’s development theories and to investigate national and Pernambuco industrial policy in selected periods. The work is based on two perspectives: 1) the manufacturing industry has a fundamental role in Pernambuco's economic growth, whether by creating jobs, by the volume produced, by exports participation, by territorial occupation, by the diffusion of new technologies, knowledges and processes; 2) The inducing role of the federal state and the interest of political players, they are decisive for the creation of an expressive industrial platform. This thesis uses the quantitative methodology to investigate the research problem, using economic data from federative entities and industrial production from selected historical periods that are displayed in time series. The data are contextualized through the theories and concepts presented throughout the work. The results of the analysis show the relevant contribution of the industry to the Pernambuco’s economy, showing paramount participation in the recent good performance. It is concluded that the cycles of favorable performance of the state’s economy are linked to a good achievement of the manufacturing sector caused by developmentalist strategies adopted by the government and political alliances.